Analysis of Bankruptcy Potential in Food and Beverage Companies Using the Altman Z-Score Due to Boycotts - Sherlyna Amara; Annisa Miftah Khofiyyan (International Journal of Quantitative Research and Modeling, 2025)
The food and beverage (F&B) industry plays an important role in the global economy, but it is highly vulnerable to geopolitical turmoil, such as boycotts arising from the Israel-Palestine conflict in the period 2023–2024. This study aims to analyze the risk of bankruptcy in multinational F&B companies affected by boycotts using a modified Altman Z-Score method, which is known to be effective in evaluating financial conditions through four key financial ratios. The data used is secondary data sourced from the annual reports of McDonald's, Starbucks, and Wendy's during the 2021–2024 period, covering the situation before and during the boycott. The results of the analysis show that McDonald's remains in the safe zone, Starbucks is classified in the danger zone, while Wendy's shows an increase from the danger zone to the grey zone. These findings indicate that the impact of boycotts on financial performance is not always significant globally because companies can adapt through efficiency strategies and financial restructuring. Overall, this study proves that the Altman Z-Score is an effective tool for predicting and assessing the financial resilience of F&B companies against external pressures such as geopolitical boycotts.